O ensino de probabilidade com o uso de mágicas fundamentadas matematicamente - Ramos, Caroline Lameza (2015)
This work has as objective to develop the basic concepts of Probability in 9th grade classes of elementary public school in the countryside of São Paulo state. In this regard, was used Mathematical Magic in order to make teaching more pleasant and meaningful, and, concurrentily we also remained the use of pedagogical instrument problem-solving techniques to the development of these activities. The theme was chosen because the fact of being little explored and worked in basic education, even though presenting applications in many areas and in everyday life. The proposals magic involved simple probability situations and practices, and search for the concepts of the tackle issue and instigate creativity, and critical thinking of learners. Thus, the proposed activities improved the mathematical knowledge of learners and developed a different dynamic, providing a greater involvement in class and consequentily providing enhancements on student performance.